Retornos à educação: uma análise da redução do diferencial salarial por anos de estudo no Brasil no período de 2001 a 2012 - Davanzo, Eloá Sales (Universidade Federal de São Carlos, 2014)
The present study aims to analyze the reduction of the wage differential by schooling in Brazil between 2001 and 2012, using the PNAD data. Although the positive relation betwee n years of schooling and earnings in the labor m arket persists, recent research on Brazilian show s that wage differentials by schooling have been falling during the past decade. Factors such as the enrollment increase in higher education (not always with q uality), and the market’s absorption of students with low productivity – or even a combination of these factors – may explain the wage differential fall. The study’s hypothesis is that the low quality of Brazilian education offers low skilled labors to the market, resulting in low productivity and lower wages even with a diploma. Using the Oaxaca - Blinder decomposition , the recent fall i n the wage differentials has been proven , as well as the returns to education. One can conclude that th e wage differentials by years of schooling in Brazil can be explained by productivity differentials, however it is not possible to identify the relationshi p between educational quality and labor productivity since the mean wages increased during the analyzed years. Therefore, the hypothesis of this study can only be partly confirmed.
Retums to Education: analysis of the wage differentials by schooling in Brazil - 2001 and 2012
Keywords: Mercado de trabalho; Retums to education; Labor market; Wage differentials; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DOS RECURSOS HUMANOS